Mundhum Discourse: Interpreting through Ethnographies of Communication - Tumbahang, Mohan Kumar (Researcher: A Research Journal of Culture and Society, 2021)
This paper attempts to see the Limbu Mundhum from the perspective of ethnography of communication model that is the factors involving in the contextual interpretation of the classical texts or ritual performances. The textual data are based on one of the main portions of the Limbu Mundhum recitation especially 'Yaapmi Pongmaa Mundhum' Origin of Man. The necessary information has been drawn from both the empirical observation as well as library studies. As this study is based on non-numerical data and endeavors to understand concepts, ideas or experiences, it typically falls under the qualitative research involving the theory of linguistic anthropology. The major finding of this paper is that a text cannot be interpreted in its fuller range of meaning unless the text is not analyzed through the ethnographies of speaking model. The paper may be helpful for the interpretation of rites and ritual performances through ethnographic perspective.